Pembinaan dan Pendampingan Perilaku Hidup Bersih dan Sehat (PHBS) di Madrasah Ibtidaiyah Hidayatul Insan Kota Palangkaraya - Nurhalina Nurhalina; Suratno Suratno; Jarot Marchel (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2017)
Household Health Survey on 2013 shows that 60% children’s disease in Palangka Raya continue to increase especially related to clean and healthy behavior. Islamic Primary School (MI) Hidayatul Insan Palangka Raya is one of primary education institution in Palangka Raya at risk of disease transmission. It is because the school has not implement clean and healthy behavior in the school environtment optimally. Clean and healthy behavior development and accompaniment in MI Hidayatul Insan Palangka Raya aimed to provide assistance to the school in planning clean and healthy behavior policy, supporting infrastructure preparation, education, observation and evaluation of clean and healthy behavior implementation. The method of the communty service involved preparation, implementation and evaluation. The output of the community service were the school has implemented clean and healthy behavior; clean and healthy school environtment; increasing student achievement; and increasing public interest to send their children to the school.